Inflation Targeting and Inflation Measurement in the Euro Area in Transition - Gunther Schnabl; Tim Florian Sepp (Wirtschaftsdienst)
Abstract Many people in the euro area increasingly feel that the general loss of purchasing power of money is much higher than the officially measured inflation rates. For example, according to survey results, perceived inflation in the first quarter of 2021 in the euro area was 4.5 %, while the officially measured inflation rate was 1 %. This could be due to the fact that price increases are subjectively perceived to be stronger than price decreases. But it could also be due to how price stability is measured and how the European Central Bank’s implementation of the price stability objective has changed.